PENGARUH KONTROL DIRI TERHADAP PROKRASTINASI AKADEMIK PADA PESERTA DIDIK KELAS XI IPS DI SMA NEGERI 2 SUNGAI RAYA - Tri Kurniasih; Purwanti Purwanti; Ana Fergina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aimed to determine the effect of self-control on students’ academic procrastination in sosical Programme (IPS) Grad XI of Senior High School 2 Sungai Raya. The Study used a descriptive quantitative method in the form of a relationship study research. Data collection techniques are indirect techniques and data collection tools using questionnaires. The data sources of this research are students of class XI IPS with a total population of 101 with 73 research samples. Based on the results of data analysis showed that the self-control of students in social programme (IPS) Grade XI of Senior High School 2 Sungai Raya was in a medium level by 79%. students’ procrastination in social programme (IPS) Grade XI of Senior High School 2 Sungai Raya was at a high lavel of 83,84%. The research findings showed that self-control affected students’ academic procrastination by 17% in sosical Programme (IPS) Grade XI of Senior High School IPS 2 Sungai Raya. It seems that there was about 83% of academic procrastination wa affected by other unknown problemsKeywords: Self Control, Students’ Academic Procrastination, Effect.